(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Basal cell carcinoma (BCC) is the most common cancer worldwide, accounts for 75% of all skin cancers, and is considered the most common malignancy in Caucasians. Major risk factors include chronic exposure to ultraviolet radiation, Fitzpatrick skin type I or II, light eyes, genetic predisposition and immunosuppressive conditions. The purpose of this study was to perform a review of the current approaches to the treatment of periorbital BCC. Over 75% of BCCs occur in the head and neck region. Furthermore, 20% of all BCCs arise in the periorbital area. BCC accounts for more than 90% of all periorbital skin cancers, grows slowly and rarely metastasizes (< 0.1%). In spite of a generally favorable prognosis and effective treatment options, BCC with aggressive local growth and deep tumor invasion can result in significant functional and cosmetic defects. According to the literature, BCC is mostly treated surgically by excising the tumor using Mohs micrographic surgery. This technique is believed to be more efficacious than conventional wide excision of the tumor or other methods of tumor excision in this anatomically difficult area of resection. The review demonstrates periorbital reconstruction after Mohs surgery for BCC is a complex task which success largely depends on collaboration of a multidisciplinary team including a dermatology oncologist, a pathomorphologist and an ophthalmic plastic surgeon. The choice of the reconstruction method depends on the size, depth and location of the defect, the status of the periorbital tissue and the surgeon’s experience. An individualized approach enables not only radical oncological treatment, but also the restoration of eyelid function and optimal esthetic outcome.